Buckling behavior of steel and steel–composite cylinders under external pressure. (December 2022) - Zuo, Xinlong; Zhang, Jian; Tang, Wenxian; Li, Yongsheng; Li, Hongyun
Abstract: This study investigated the buckling behavior of steel and steel–composite cylinders under external pressure. The steel cylinders had a length-to-diameter ratio of 2.01 and a thickness-to-diameter ratio of 0.0094. The external surfaces of the steel cylinders closed using two heavy bungs were blasted with grit. The steel–composite cylinders were fabricated by wrapping [55 ∘ / − 55°]4 composite layer on the steel cylinders. The total thickness-to-diameter ratio of the steel–composite cylinders was 0.0170. Three nominally identical steel cylinders and three nominally identical steel–composite cylinders were designed, fabricated, geometrically measured, and hydrostatically tested. Linear eigenvalue and nonlinear RIKS analyses were performed to evaluate the buckling behavior of fabricated cylinders. The experimental and numerical data agreed well with each other. The average ultimate strength of the steel–composite cylinders was 2.853 MPa, which is 1.838 times that of steel cylinders. These findings indicate that the steel cylinders can be considerably strengthened by wrapping composite materials. Furthermore, the steel–composite cylinders were slightly less sensitive to large imperfections compared with steel cylinders. Highlights: Buckling behavior of steel and steel–composite cylinders were experimentally explored. Wrapping CFRP layers considerably enhanced the loading capacity of steel cylinder. RIKS method could reasonably estimate buckling of steel and steel–composite cylinders. Effect of initial geometric imperfection size on ultimate strength were numerically explored. Numerical and experimental data exhibited satisfactory agreement.